As jovens mulheres na educação de jovens e adultos e a constituição de seus projetos de vida - Maria de Fátima Pereira Carvalho (2021)
This thesis investigates life projects of young women inserted in the segment II of Youth and Adult Education of the public school system in the city of Guanambi, located in the High Backlands of Bahia, Brazil. From a technical-methodological point of view, throughout 2017 and 2019, discussion groups were held with a broader group of young collaborating female from whom five of them were submitted to a semi-structured personalized interview. The main objective of this research is to know the life projects of these young women, verifying to what extent schooling takes part in them. To reach that aim, it is identified the age, racial and professional profile of young women enrolled in EJA Public school system in the city of Guanambi; part of their life projects are described, highlighting and analyzing the ways and place these projects take part in their lives and how schooling fits into their plans. The understanding of the data is based on the assumptions of a qualitative approach. Theoretically, the research is based on the feminist studies that address issues of gender and schooling (BARBOSA, 2013; DAVIS, 2016; HIRATA, 2014; KABEYA, 2010; LEONCY, 2013; LOURO, 1997; MARQUES, 2019; MATOS, 2008; NARVAZ; SANT’ANNA TESSELER, 2013; SCOTT, 1990; SILVA, 2017; SILVA, 2018; SOUZA, 2015) and on studies on youth and life projects (ABRAMO, 2007; CARRANO, 2007; DAYRELL, 2005; PAIS, 1993). The data analysis demonstrates that, by sharing part of their trajectories and life projects, the understanding of what it is to be a woman in Brazilian society is linked to the intersection among class, race/ethnicity, gender and generation. The research results also indicates that the young women attending EJA are not just any women, they are young, women, poor, mostly black, northeastern, who go through confrontations to stay in school and naturalize the culture of suffering. Although surrounded by challenges that prevent them from making certain choices, they present experiences that go beyond the established ways of being male and female and experience other ways of being, existing and acting amid taboos of the social environment in which they are inserted. Issues related to racism, discrimination against women, teenage motherhood and violence have directly affected young female students attending EJA education in the city of Guanambi/BA.